PENGARUH KINERJA KEUANGAN DAN INFLASI TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR (Studi Kasus Pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2010-2012) - Maria Fransisca Widyaningsih, 09.05.52.0014 (Students Journal of Accounting and Banking, 2013)
The study aims to test the effect of financial performance and inflation on stock price on manufacturing company listed in Indonesia Stock Exchange from 2010 to 2012. Company performance is calculated using the ratio of Return on Equity (ROE), Debt to Equity Ratio (DER), Earning Per Share (EPS).The population in this study is a manufacturing company listed on the Stock Exchange in 2010-2012 as many as 126 manufacturing companies. Samples are determined by purposive sampling technique, the sample in this study was 65 manufacturing companies. Data analysis techniques in the research Ordinary Least Squares regression (OLS). The analysis showed that the ROE significant negative effect, DER positive effect was not significant, EPS significant positive effect, and significant negative effect of inflation.Keywords: ROE, DER, EPS, Inflation and Stock Price